PENERAPAN ERROR CORRECTION MECHANISM DALAM PEMODELAN PERTUMBUHAN EKONOMI PROVINSI JAWA TIMUR TAHUN 2005-2021 - Lukman Huq Mahmuda Siregar; Muhammad Rizky (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The economy of East Java Province, as indicated by the Gross Domestic Regional Product (GDRP), experienced a contraction due to the Covid-19 pandemic by 2.33 percent. The shock will disrupt the stability of the East Java economy if it is not handled quickly and accurately. This study aims to establish an appropriate model for analyzing economic growth through GDRP in East Java by using the independent variables Human Development Index (IPM), Gross Fixed Capital Formation (PMTB), GDRP of Manufacturing Industry Sector (IP), and Regional Minimum Wages (UMR) using the Error Correction Mechanism (ECM) model to obtain long-term and short-term relationships of these variables. The results showed that the IPM, PMTB, and UMR had a positive and significant relationship with GDRP in the long term, while the IP variable had a positive but not significant relationship with GDRP in the long term. In the short term, IPM, PMTB, IP, and UMR have a positive and significant relationship with GDRP. In addition, there is an Error Correction Term (ECT) coefficient of -0.8917 which means that the influence of the IPM, PMTB, IP and UMR variables will be corrected by 89.17 percent toward long-term balance in each period